Financial Literacy for the Future: Preparing Individuals for Economic Success - Amirtha, R. (Recent Research Reviews Journal, 2024)
Financial literacy encompasses the knowledge and skills essential for making informed financial decisions, impacting both personal and professional lives. This study explores the significance of financial literacy in navigating today's complex financial landscape, emphasizing its role in budgeting, saving, investing, debt management, retirement planning, and understanding financial products. It highlights the necessity of financial literacy for achieving financial stability, independence, and overall well-being, as well as its contribution to a stronger economy. Case studies, such as a family's successful debt reduction strategy and a business's effective budgeting process, illustrate how financial literacy leads to improved outcomes. The findings highlight the need for targeted financial education programs and policies that can bridge knowledge gaps and empower individuals to make better financial choices. The study reviews existing literature on financial literacy, noting disparities in knowledge across demographics and the challenges in translating knowledge into effective financial behavior. Ultimately, improving financial literacy is integral to enhancing economic well-being and fostering more equitable financial systems.
Keywords: Financial Behavior; Income; Expense; Financial Independence; Money Management; Risk Tolerance; Financial Decision Making